Greening of the boreal peatland food web: Periphyton supports secondary production in northern peatlands. Issue 5 (19th March 2021) - Ferguson, Hannah M.; Slagle, Elizabeth J.; McCann, Ann Ashlea; Walls, Jeremy T.; Wyatt, Kevin H.; Rober, Allison R.
Abstract: Characterizing spatial and temporal variability of food web dynamics is necessary to predict how wetter and more nutrient‐rich conditions expected with climate change will influence the fate of organic matter within northern peatlands. The goals of this study were to (1) document spatial and temporal variability in the contribution of periphyton to peatland food webs using isotope analysis ( 13 C and 15 N), and (2) quantify the influence of increased nutrient availability on primary and secondary production across a gradient of rich, moderate, and poor fen peatlands common to the northern boreal biome. We established replicate m 2 plots within each fen located in interior Alaska to quantify periphyton (algae and bacteria) and macroinvertebrate biomass with and without nutrient addition throughout a growing season (May–August). Stable isotope analysis showed that periphyton contributed x ¯ = 65% of organic matter to the food web over time and across fens compared to x ¯ = 7% from plants or detritus. The transfer of basal resources was reflected in an increase in herbivore biomass as algal biomass increased over time in all fens, followed by an increase in predatory macroinvertebrates during the latter part of the growing season. Furthermore, all measures of periphyton and macroinvertebrate biomass were enhanced by nutrient addition. These data provide insight into patterns of natural variation within the aquatic food web of boreal peatlands and show that basal resources within this ecosystem, which are generally considered to be "detritus‐based, " are actually driven by periphyton with minimal input from plant detrital pathways.